"Language is a darkness pulled out of us": using poetry to improve literacy in adults with histories of addiction and trauma. Issue 4 (2nd October 2022) - Lynch, Jenna L.
ABSTRACT: Adult students with histories of addiction or trauma may face difficulties in the classroom. Poetry can be used as a motivational tool for adult students, and as a means of understanding and expressing complex emotions and experiences. Despite a plethora of research on the effects of poetry on adults in treatment and rehabilitation centers, little research has been conducted in educational settings. This article reviews the literature on poetry and adults with histories of addiction or trauma and offers classroom considerations and writing exercises for the poetry workshop.